Recurrence of pancreatic cancer presented as cervical lymphadenopathy. Issue 1 (December 2015) - Nagata, Hiroshi; Hayashi, Ken; Yamada, Shigetoshi
Abstract Background We report a case of recurrent pancreatic cancer that presented as cervical lymphadenopathy. Case presentation A 69-year-old woman with stage IIb pancreatic cancer underwent a curative Whipple's procedure after neoadjuvant chemoradiation therapy. Despite adjuvant chemotherapy with S-1, postoperative recurrence was diagnosed as left cervical lymphadenopathy 11 months postoperatively. After she underwent chemoradiation therapy to the cervical area followed by systemic chemotherapy with S-1, the lymphadenopathy became unremarkable 17 months postoperatively. S-1 treatment was discontinued 23 months postoperatively at the patient's request. She has remained free of disease since that time and has achieved an overall duration of survival of 48 months. Conclusions To the best of our knowledge, this is the first reported case of middle cervical lymph node metastasis of pancreatic cancer. Although rare, it should be considered as a site of recurrence. This case suggests concurrent radiation therapy can be a good option for patients who cannot tolerate an aggressive regimen.